Penguatan Kedudukan Peraturan Desa Dalam Sistem Perundang-Undangan Indonesia - Wardana, Dodi Jaya (Jurnal Justiciabelen, 2020)
In Law Number 10 of 2004, Village Regulations are placed as one of the types of Legislation in Indonesia. However, with the birth of Law Number 12 of 2011 concerning the Establishment of Legislation as a substitute for Law Number 10 of 2004 the position of Village Regulations became unclear, even unregulated and not included in the hierarchical system of Legislation in Indonesian. Village Head Regulations, which are the implementing rules of Village Regulations, and are positioned under Village Regulations, are more regulated and incorporated into the Indonesian Legislation System. Furthermore, in Law Number 12 of 2011, regulations regarding hierarchy or position / position of Village Regulations are not regulated. If carefully explored in Law Number 12 of 2011, there is no position in the Village Regulations as a type and explicitly in the hierarchy of Legislation. Therefore, this research is expected to clarify and reinforce the position or position of village regulations in Indonesian legislation. So that Village Regulations can be one of the rules of the Indonesian legislation.